Increased permeability of human endothelial cell line EA.hy926 induced by hantavirus-specific cytotoxic T lymphocytes - Hayasaka, Daisuke; Maeda, Ken; Ennis, Francis A.; Terajima, Masanori (Virus research, 2007)
Hantavirus infection causes two human diseases, hemorrhagic fever with renal syndrome and hantavirus pulmonary syndrome. The typical feature of these diseases is increased permeability in microvascular beds in the kidneys and the lungs, respectively. The mechanism of capillary leakage, however, is not understood. Some evidence suggests that hantavirus disease pathogenesis is immunologically mediated by cytotoxic T lymphocytes and other immune cells in target organs producing inflammatory cytokines. In this study we examined the roles of virus-specific cytotoxic T lymphocytes in increased permeability of human endothelial cells infected with hantavirus. We used a human CD8 + hantavirus-specific cytotoxic T lymphocyte line, 1A-E2, specific for the HLA-A24-restricted epitope in Sin Nombre and Puumala virus G2 protein, and the human endothelial cell line, EA.hy926 that expresses HLA-A24 molecule. The cytotoxic T lymphocyte line recognized and lysed target cells infected with Sin Nombre virus, and in transwell permeability assays increased permeability of EA.hy926 cell monolayer infected with Sin Nombre virus or recombinant adenovirus expressing the Sin Nombre virus G2 protein. These results suggest that cytotoxic T lymphocyte activity contribute to capillary leakage observed in patients with hantavirus pulmonary syndrome or hemorrhagic fever with renal syndrome.